Use of Artificial Intelligence in Learning: Analysis of Effectiveness and Potential in Improving the Quality of Learning - Miftahus Surur; Bernadetha Nadeak; Ni Made Rianita; Ni Nyoman Ari Ratnadi; Suparjan Suparjan; Bincar Nasution; Alex Primo (Jurnal Ilmu Pendidikan, 2024)
The concept of artificial intelligence (AI) has become inextricably linked to the technological developments occurring within the context of the Industry 4.0 and Society 5.0 eras. AI can be defined as a computer program comprising integrated machine learning, hardware, and software components. This concept of AI draws inspiration from the neocognitron patterns observed in the human brain and employs knowledge derived from hardware and software in order to fulfil its functions. With the advent of Industry 4.0, AI has been increasingly utilized in diverse domains, including education. The objective of this research is to elucidate the role of AI in education during the Industry 4.0 era, employing qualitative research methodologies. In the context of education, AI facilitates personalized learning experiences tailored to individual learners. AI systems assist educators in designing individualized learning profiles, encompassing a range of practical exercises, for each learner. This permits the adaptation of learning materials to align with the abilities, learning styles, and experiences of each learner. The implementation of AI technology in education is considered beneficial, facilitating the tasks of educators, particularly those related to administration, such as assessment and determining final grades based on applicable weights and evaluations. Furthermore, AI technology has the potential to enhance the quality of active and interactive learning experiences, thus facilitating the teaching-and-learning process for educators and learners alike..